2009
DOI: 10.1002/hyp.7439
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of a Penman–Monteith type equation to estimate reference evapotranspiration in southern Spain

Abstract: Abstract:Sensitivity analysis is crucial in assessing the impact of climatic variables on reference evapotranspiration estimations. The sensitivity of the standardized ASCE-Penman-Monteith evapotranspiration equation for daily estimations to climatic variables has not yet been studied in Spain. Andalusia is located in southern Spain where almost 1 million ha are irrigated under quite different conditions; it has a high inter-annual variability in rainfall. In this study, sensitivity analyses for this equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 27 publications
7
55
1
Order By: Relevance
“…In general, Ep was more sensitive to net radiation, followed by air temperature, relative humidity, and wind speed (Figure 8). The results for Ep are not directly comparable to those of previous works, due to the differences of the equations being utilized, of the study media, of the varied approaches to conducting the sensitivity analyses, and of the derived and defined sensitivity coefficients (Estévez et al, 2009). Some other studies (McCuen, 1974;Saxton, 1975;Coleman and DeCoursey, 1976;Beven, 1979) showed that potential evaporation (or evapotranspiration) was much more sensitive to radiation, humidity, and temperature.…”
Section: Discussioncontrasting
confidence: 64%
“…In general, Ep was more sensitive to net radiation, followed by air temperature, relative humidity, and wind speed (Figure 8). The results for Ep are not directly comparable to those of previous works, due to the differences of the equations being utilized, of the study media, of the varied approaches to conducting the sensitivity analyses, and of the derived and defined sensitivity coefficients (Estévez et al, 2009). Some other studies (McCuen, 1974;Saxton, 1975;Coleman and DeCoursey, 1976;Beven, 1979) showed that potential evaporation (or evapotranspiration) was much more sensitive to radiation, humidity, and temperature.…”
Section: Discussioncontrasting
confidence: 64%
“…The optimal parameters for the best model performance could then be determined with the highest value of NSeff. The model sensitivity to systematic and random errors in a and b was evaluated according to [40,41]. Briefly speaking, the i-th perturbed data value (X ip ) is the sum of the i-th original value (X io ), a constant systematic bias (E s ), and a random error with zero-mean and normally distribution (E r ):…”
Section: Sensitivity Testmentioning
confidence: 99%
“…With its simplicity and intuitionism, the method is popular and has been widely used (Ahn, 1996;Goyal, 2004;Xu et al, 2006a, b;Estévez et al, 2009 , 1997). In the study, a crop's GDD was calculated per year, following the most widely used "Method 1" (McMaster and Wilhelm, 1997), by summing the difference of the daily base temperature and the average air temperature over the reference crop-growing period in days (Table 1).…”
Section: Sensitivity Analysismentioning
confidence: 99%